Networks, work, and inequality - McDonald, Steve (Bingley, U.K. : Emerald, 2013)
The importance of social relationships at work has long been recognized in the social sciences. Interest in this topic has been renewed through scholarly and popular discussions of social capital as well as recent innovations in network data collection and analysis. These developments have allowed researchers to ask a variety of new questions about the role of networks in the world of work and a multitude of approaches to answering those questions. While several monographs have been written on issues related to networks and work, none has simultaneously brought together the range of approaches used to explore this topic. Furthermore, this volume is the first to merge this focus on networks and work with a sociological perspective on inequality. Specifically, the chapters illuminate the processes by which social networks in work organizations can effectively generate, sustain and ameliorate social inequalities across individuals, firms, and occupational fields. In doing so, this volume offers valuable insights that inform researchers and policy makers alike regarding issues of workplace discrimination, diversity and innovation.
Frontiers of sociological research on networks, work, and inequality / Steve McDonald ... [et al.] -- What might a labor market look like? / Donald Tomaskovic-Devey -- Race, network hiring, and statistical discrimination / Roberto M. Fernandez, Jason Greenberg -- Social networks, job search, and job earnings in a transitional economy : an institutional embeddedness argument / Wei Zhao -- Consent and the subjective world of the worker / Marty Laubach, Michael Wallace -- The network-organized labor process : control and autonomy in web production work / Amanda K. Damarin -- Employee morale and organizational climate in schools : the importance of affective coworker relationships / Heather E. Price -- Gender inequality and the structure of occupational identity : the case of elite sociological publication / Ryan Light -- Social capital and work activity : autonomy, supervision, and creativity in interpersonal networks / Richard A. Benton -- Structural embeddedness of accessed networks and innovation at work / Ray-May Hsung, Yi-Jr Lin, Ke-Wei Lu -- Institutional embeddedness of network embeddedness in the workplace : social integration at work and employee's health across three societies / Lijun Song -- Forms of social capital : family resources, campus networks, and dominant class advantage at an elite university / Nathan D. Martin -- Jumping ship or merely crossing the aisle? : an analysis of the circulation of elite lawyers / Debra Schleef.
Keywords: Social Science -- Sociology -- General; Social Science -- Research; Social Science -- General; Sociology: work & labour; Office & workplace; Industrial sociology; Work